2011
DOI: 10.1097/bco.0b013e31821cd636
|View full text |Cite
|
Sign up to set email alerts
|

The arthroscopic treatment of cyclops syndrome

Abstract: BackgroundCyclops syndrome is caused by a scar tissue nodule adjacent to the tibial tunnel of the anterior cruciate ligament graft after surgery. These lesions result in pain and loss of extension with impingement of the lesion. The goal of this series is to present our 10-year experience with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Out of 60 patients, 68.4% were ranked as good or excellent. In the literature, the postoperative Lysholm score in the cyclops syndrome ranges between 91.5 and 94.1 points [11,33], while in other surgical procedures used for the elimination of knee adhesions, only 82 points [12]. In our earlier papers [35][36][37][38], this value ranged between 93 and 97 points, which indicated that cyclops lesion is a complication that significantly compromises the average results of ACL reconstruction.…”
Section: Ristić V Et Al Cyclops Syndrome After Acl Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 60 patients, 68.4% were ranked as good or excellent. In the literature, the postoperative Lysholm score in the cyclops syndrome ranges between 91.5 and 94.1 points [11,33], while in other surgical procedures used for the elimination of knee adhesions, only 82 points [12]. In our earlier papers [35][36][37][38], this value ranged between 93 and 97 points, which indicated that cyclops lesion is a complication that significantly compromises the average results of ACL reconstruction.…”
Section: Ristić V Et Al Cyclops Syndrome After Acl Reconstructionmentioning
confidence: 99%
“…Cyclops lesion can be prevented by adequate removal of all ruptured ligament fibers, positioning the bone tunnels in bones, avoiding fiber damage [11,12] and early rehabilitation, which aims to achieve full extension and flexion of at least 90 degrees during the first postoperative month [9,10]. If the lesion causes pain and movement restriction, predominantly in knee extension, arthroscopic knee debridement is necessary [6,7,11,12].…”
Section: Ristić V Et Al Cyclops Syndrome After Acl Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation